Tailoring feedback and messages to encourage meat consumption reduction - Schnabelrauch Arndt, Chelsea A. (Kansas State University, 2016)
Though the research on vegetarianism and meat consumption reduction has dramatically increased over the last few decades, almost all of this research focuses on current vegetarians/meat reducers and non-vegetarians’ perceptions of vegetarianism (Boyle, 2007; Ruby, 2012). Research targeting non-vegetarians and attempting to influence their meat consumption is virtually non-existent. Thus, the intent of the present dissertation was to effectively decrease individuals’ meat consumption habits and alter individuals’ attitudes toward meat. As research has repeatedly found that messages that are tailored to an individual are more persuasive and effective at influencing health behaviors (Bull et al., 2001; Ryan & Lauver, 2002)) and attitudes (e.g., Murray-Johnson & Witte, 2003; Rimal & Adkins, 2003), the present dissertation specifically sought to determine the effectiveness of tailored meat consumption reduction feedback and messages to influence individuals’ intentions to consume meat and attitudes toward meat consumption. Specifically, this dissertation investigated the effectiveness of messages specific to individuals’ behavior (a behavioral feedback approach), messages oriented to individuals’ self-schemas, egoistic and altruistic oriented messages, and feedback/messages tailored to individuals’ values. Contrary to the hypotheses, the results of the present studies suggested that individuals’ willingness to reduce their meat consumption is not differentially affected by different types of feedback/messages; however, this lack of significant impact for tailored feedback/messages may due to various limitations that are discussed at length within the present dissertation. Despite the possible limitations of the studies conducted, the present dissertation has made significant contributions to the meat consumption reduction literature. The first of its kind, this dissertation importantly illustrates the importance of and need for research encouraging meat consumption reduction.
Keywords: Attitudes; Persuasion; Tailoring messages; Meat consumption; Social psychology; Experimental psychology